Metal Complexes for Two‐Photon Photodynamic Therapy: A Cyclometallated Iridium Complex Induces Two‐Photon Photosensitization of Cancer Cells under Near‐IR Light. Issue 2 (2nd November 2016) - McKenzie, Luke K.; Sazanovich, Igor V.; Baggaley, Elizabeth; Bonneau, Mickaële; Guerchais, Véronique; Williams, J. A. Gareth; Weinstein, Julia A.; Bryant, Helen E.
Abstract: Photodynamic therapy (PDT) uses photosensitizers (PS) which only become cytotoxic upon light‐irradiation. Transition‐metal complexes are highly promising PS due to long excited‐state lifetimes, and high photo‐stabilities. However, these complexes usually absorb higher‐energy UV/Vis light, whereas the optimal tissue transparency is in the lower‐energy NIR region. Two‐photon excitation (TPE) can overcome this dichotomy, with simultaneous absorption of two lower‐energy NIR‐photons populating the same PS‐active excited state as one higher‐energy photon. We introduce two low‐molecular weight, long‐lived and photo‐stable iridium complexes of the [Ir(N^C)2 (N^N)] + family with high TP‐absorption, which localise to mitochondria and lysosomal structures in live cells. The compounds are efficient PS under 1‐photon irradiation (405 nm) resulting in apoptotic cell death in diverse cancer cell lines at low light doses (3.6 J cm −2 ), low concentrations, and photo‐indexes greater than 555. Remarkably1 also displays high PS activity killing cancer cells under NIR two‐photon excitation (760 nm), which along with its photo‐stability indicates potential future clinical application. Abstract : Irradiating iridium : Two low‐molecular‐weight, long‐lived, and photo‐stable iridium complexes of the [Ir(N^C)2 (N^N)] + family with high two photon‐absorption are shown to localise to mitochondria and lysosomal structures in live cells. The compounds are efficient photosensitizers (PS) under 1‐photon irradiation (405 nm) with photo‐indices greater than 555. Remarkably, 1 also displays high PS activity under NIR two‐photon excitation (760 nm) indicating potential future clinical application.